2016
DOI: 10.3390/su8010079
|View full text |Cite
|
Sign up to set email alerts
|

Commercially Available Materials Selection in Sustainable Design: An Integrated Multi-Attribute Decision Making Approach

Abstract: This paper presents an integrated multi-attribute decision-making (MADM) approach to aid selection of commercially available materials in the context of sustainable design. The MADM couples grey relational analysis (GRA) with an analytic hierarchy process (AHP) to rank alternative materials in terms of their economic, environmental, and social performance. AHP is used to determine the corresponding weighting values for the selected indicators. In addition, a case example is used to verify the proposed MADM met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 78 publications
0
39
0
Order By: Relevance
“…Consequently, MADM methods, such as analytic hierarchy process (AHP) and grey relational analysis (GRA) are able to rank material alternatives and help designers determine the best material. A paper introduces a computational approach for materials selection in the context of green design by using GRA, integrated with AHP [18]. Another paper used information entropy analysis and GRA to analyze the changes in water utilization structure and its impact factors using water consumption data for agricultural, industrial, domestic, and ecological areas in the city of Tianjin [14].…”
Section: Methodologies Of Energy Economics and Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, MADM methods, such as analytic hierarchy process (AHP) and grey relational analysis (GRA) are able to rank material alternatives and help designers determine the best material. A paper introduces a computational approach for materials selection in the context of green design by using GRA, integrated with AHP [18]. Another paper used information entropy analysis and GRA to analyze the changes in water utilization structure and its impact factors using water consumption data for agricultural, industrial, domestic, and ecological areas in the city of Tianjin [14].…”
Section: Methodologies Of Energy Economics and Managementmentioning
confidence: 99%
“…Some studies have focused on materials selection by market demand, while others have found that materials selection is also motivated by cost considerations. However, most studies have not treated environmental management as a key aspect of materials selection in product design [18]. Thus, a paper in this special issue presents an integrated multi-attribute decision-making (MADM) approach to aid selection of commercially-available materials for sustainable design.…”
Section: Important Issues For China's Energy Economics and Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…The life-cycle assessment aims to measure the total pollution associated with a product throughout its lifecycle (gronlund et al, 2015). however, it is complicated for engineers to implement in real application, because of the intricate boundary division, inconvincible data acquisition Zhao et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…It is used to empirically measure productive efficiency of decision-making units (DMUs). Moreover, the low-carbon economy performance evaluation by TFP has rapidly expanded to include carbon emission calculations [11][12][13], carbon emission influence analysis [14][15][16], industrial carbon emission [17][18][19][20], and carbon emission reduction [21][22][23][24]. Meanwhile, regional diversity plays a key role in the processing of low-carbon emission transformation.…”
Section: Literature Reviewmentioning
confidence: 99%